Combination gut microbiota modulation and chemotherapy for orthotopic colorectal cancer therapy. (December 2021) - Chen, Zhao-Xia; Li, Jiang-Lan; Pan, Pei; Bao, Peng; Zeng, Xuan; Zhang, Xian-Zheng
Abstract: Gut microbiota is closely related to the tumorigenesis and progression of colorectal cancer (CRC), especially Fusobacterium nucleatum ( Fn ) could promote colorectal tumor growth and cause chemoresistance. Here, we developed a tumor-triggered release drug delivery gel to inhibit CRC cell growth in situ by intestinal perfusion. Antibiotic metronidazole (MTZ) and 5-fluorouracil (5-FU), the first-line chemotherapy drug of CRC, are individually incorporated into metal polyphenol network-coated mesoporous silica nanoparticle (MSN), and then blended with carboxymethyl cellulose (CMC) to obtain an anti-CRC gel, AB-Gel. In vivo studies showed that AB-Gel could efficiently inhibit the growth and metastasis of CRC in an orthotopic mouse model attributing to the MTZ-induced modulation in the CRC-related microbiota. Chemotherapy efficacy against orthotopic CRC was significantly enhanced by the elimination of Fn . This strategy based on the combination of gut microbiota modulation and chemotherapy would be considered as an enhanced strategy for CRC treatment with potential use in the clinic. Graphical Abstract: A colonic perfusion gel with tumor-triggered drug release ability was designed for colorectal cancer therapy using combination of gut microbiota modulation and chemotherapy. ga1 Highlights: Developing a drug delivery gel (AB-Gel) to inhibit colorectal cancer (CRC) in situ by intestinal perfusion. AB-Gel can inhibit CRC in orthotopic mouse model due to the combined effect of antibacterial and anticancer. AB-Gel can form a sticky layer on colonic mucosa and prolong drug release time.